Prognostic value of patient-reported outcomes for survival in patients with advanced lung cancer receiving immune checkpoint inhibitors - Gandara, David; Gogishvili, Miranda; Sezer, Ahmet; Makharadze, Tamta; Gümüş, Mahmut; Zhu, Cong; Yan, Eric; Gullo, Giuseppe; Rietschel, Petra; Quek, Ruben G. W. (Frontiers in Immunology, 2025)
IntroductionThere is potential clinical utility in using patient-reported outcomes (PROs) to predict survival in patients with advanced non-small cell lung cancer. We assessed the prognostic value of PROs for survival in two phase 3 cemiplimab studies in advanced non-small cell lung cancer.MethodsData from EMPOWER-Lung 1 and EMPOWER-Lung 3 Part 2, two global, randomized phase 3 clinical trials, were used. Patients with advanced non-small cell lung cancer and programmed cell death-ligand 1 expression ≥50% received cemiplimab monotherapy (n=283), and patients with no EGFR, ALK, or ROS1 genomic aberrations received cemiplimab plus chemotherapy (n=312). PROs were assessed using the European Organization for Research and Treatment of Cancer Core Quality of Life and Quality of Life Lung Cancer 13 questionnaires. Association between baseline PROs and survival was analyzed, and the C-statistic was used to assess the prognostic value of PROs in comparison with the Eastern Cooperative Oncology Group performance status (ECOG PS) scale.ResultsTwenty-five PROs were evaluated, of which 15 were significantly associated (P<0.05) with overall survival and were better predictors than ECOG PS. Fourteen PROs were significantly associated (P<0.05) with progression-free survival; of these, 13 had better prognostic value than ECOG PS. Patient-reported dyspnea and physical functioning had the highest prognostic values for overall survival (c=0.635 and c=0.619, respectively) and progression-free survival (c=0.593 and c=0.583, respectively). Stratifying physical functioning into high, medium, and low categories showed that patients with high physical functioning at baseline had significantly better overall survival (high vs low; HR, 0.41; 95% CI, 0.23-0.71; P=0.001), resulting in a 59% reduction in the risk of death. Similarly, patients in the high physical functioning category had significantly favorable progression-free survival (high vs low; HR, 0.44, 95% CI, 0.29-0.66; P<0.001) and a 56% reduction in the risk of death.ConclusionBaseline PROs, including dyspnea and physical functioning, have significant prognostic value for survival for patients with advanced non-small cell lung cancer.